The Similarities and Differences of Jo March’s Character in The Novel and Film of “Little Women” - Saputra, Septian Bimo; Nurholis, Nurholis; Sariyati, Ice (Universitas Negeri Padang, 2024)
Literary adaptation involves changes in the process of transferring some elements from the source text into the new medium, one of the examples is the adaptation of the narrative elements such as the main character. This study analyzes the adaptation process from the novel Little Women by Louisa May Alcott adapted to the film Little Women by Greta Gerwig the main purpose of the research is to analyze the similarities and differences found in Jo March's character between the novel and its film adaptation. This study used the qualitative descriptive method combined with the theory of adaptation by Hutcheon (2013). The findings of this study were the narrative elements adapted, namely Jo March as the main character in the novel and film. In conclusion, the similarities and differences found in Jo March’s character from the novel and film were the consequences of the process of adaptation that involved some adjustments to fit with the new medium.